MATHEMATICAL MODELLING OF MACROSEGREGATION IN INGOT CASTING - Assunção Jr, M. O.; Vynnycky, M. (Revista de Engenharia Térmica, 2018)
The occurrence of macrosegregation in alloys produced by ingot casting can adversely affect the quality of the final product. Macrosegregation can be described as a severe variation on the macroscopic scale of the chemical species that compose the alloy, and the ability of computational simulations to predict such defects remains far from perfect. Therefore, this research focuses on the development of a two-dimensional mathematical model that - through computational simulations - could be applied to study and predict the formation of macrosegregation in the ingot casting of binary alloys. Once accomplished, this work can establish the framework to new studies that will tackle more advanced problems, e.g., for actual ingot geometries, three-dimensional models and industrially-important ternary alloys.